A rare case of spiradenoma or a common sebaceous cyst? - A case study - Kłos, Nikola; Boblewska, Justyna; Szepelska, Ada; Bienia, Grzegorz; Kosowski, Tomasz; Kondratskyi, Vitalii; Sygnowski, Michał; Jędrys, Wiktoria; Sowińska, Izabela (Journal of Education, Health and Sport, 2024)
Spiradenoma is a rare and adnexal skin tumor of the sweat gland appearing equally frequently in both female and male patients. When having a patient with a solitary, nodule occurring on a scalp, a spiradenoma diagnosis should be considered. However, it always ought be differentiated with more common skin lesions e.g. sebaceous cyst. This case report presents a 36 year old male presented with a solitary 1,5 centimeter in diameter mass on the scalp of the left temporal region. The patient underwent an ultrasound and excision biopsy which revealed spiradenoma diagnosis. This tumor transforms into malignant form extremely rarely. However, transformation is more likely in elderly patients having a long-standing lesions This is why early and wide excision is crucial and considered to be a gold standard treatment.